2010
DOI: 10.1002/zoo.20340
|View full text |Cite
|
Sign up to set email alerts
|

Energy digestibility of giant pandas on bamboo‐only and on supplemented diets

Abstract: Endangered giant pandas (Ailuropoda melanoleuca) are bears (Family Ursidae), within the order Carnivora. They specialize on an herbivorous diet of bamboo yet retain a gastrointestinal tract typical of their carnivorous ancestry. The evolutionary constraints of their digestive tract result in a low extraction efficiency from bamboo (<40% in reported studies). The goal of this study was to determine the energy digestibility of bamboo by giant pandas used in digestibility trials and through subsequent analyses wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 16 publications
1
19
0
Order By: Relevance
“…Clearance of the digesta is generally observed between 5 and 12 h (Dierenfeld et al, 1982;Mainka et al, 1989;Edwards et al, 2006;Senshu et al, 2007), although longer times have been reported in pandas with intestinal disorders (Mainka et al, 1989;Senshu et al, 2007) or depending on the portion of bamboo ingested [about 8 h for shoots, 10 h for stems and 14 h for leaves (Schaller et al, 1985)]. The low digestibility of bamboo by pandas [<40% on either a dry matter or apparent energy conversion basis (Dierenfeld et al, 1982;Senshu et al, 2007;Sims et al, 2007;Finley et al, 2011)], raised some questions over the evolutionary advantage of moving to such a diet (Gittleman, 1994). How giant pandas meet their nutritional and energetic requirements has not been fully resolved, particularly when compared to other large herbivores.…”
Section: Introductionmentioning
confidence: 99%
“…Clearance of the digesta is generally observed between 5 and 12 h (Dierenfeld et al, 1982;Mainka et al, 1989;Edwards et al, 2006;Senshu et al, 2007), although longer times have been reported in pandas with intestinal disorders (Mainka et al, 1989;Senshu et al, 2007) or depending on the portion of bamboo ingested [about 8 h for shoots, 10 h for stems and 14 h for leaves (Schaller et al, 1985)]. The low digestibility of bamboo by pandas [<40% on either a dry matter or apparent energy conversion basis (Dierenfeld et al, 1982;Senshu et al, 2007;Sims et al, 2007;Finley et al, 2011)], raised some questions over the evolutionary advantage of moving to such a diet (Gittleman, 1994). How giant pandas meet their nutritional and energetic requirements has not been fully resolved, particularly when compared to other large herbivores.…”
Section: Introductionmentioning
confidence: 99%
“…nuda ) were selected for nutritional analysis as these species were of the same genus and preferred by giant pandas throughout the year (Kouba, personal observation). These four species are all endemic to China, and are a common diet staple for many giant pandas in the U.S. [7, 36]. Following harvest, bamboo was stored in a misted cooler for no more than 3 days prior to feeding.…”
Section: Methodsmentioning
confidence: 99%
“…Although the giant panda exhibits morphological and physiological adaptations that allow it to process this woody plant for its diet, the giant panda retained the relatively short gastrointestinal tract (GIT) of a carnivore and a rapid digesta passage rate of 6–12 h [4, 5]. The giant panda’s GIT also lacks specialized compartments, such as a rumen or cecum, required for extensive fermentation; hence, their ability to digest and utilize nutrients from bamboo is considerably reduced (dry matter digestibility ranges from 6.9 to 19.6%) [4, 6, 7]. Dierenfeld [8] suggested that the energy requirements of the giant panda ranged from 3,100 to 5,700 kcal/d.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies show that the nutritional value varies greatly in different parts of the bamboo body 10–13 . Moreover, the bioavailability of different plant parts varies significantly 14, 15 . So, if the consumption of single-parts continues for a long period of time, it may potentially lead to nutritional imbalances and negatively impact the health of giant pandas.…”
Section: Introductionmentioning
confidence: 99%